A NARRATIVE INQUIRY STUDY ON LANGUAGE LEARNING THROUGH POP UP BOOK - Fais Wahidatul Arifatin (Jurnal Bahasa Lingua Scientia, 2022)
This research is a narrative inquiry research that focuses on students' perceptions and experiences in language learning using a pop-up book. The use of media in learning is considered very important so that researcher focused on language learning by using realia media in the form of pop-up books. Narrative inquiry research is a form of qualitative research in which researcher obtains data from documentation and student interviews. This research was conducted at MTs Muhammadiyah 13 Solokuro, at the 7th grade level with a total of 9 students. The study took place from March to May 2022. The results of this study indicate that students have a good perception of language learning using pop-up and of course they have new experiences with the methods applied in the learning. There have been many studies on the development and application of a method in learning, while this time the researcher choses to look for something different by looking at the stories, perceptions and experiences of students.